A terceirização da armazenagem em um third-party logistics: um estudo de caso da Kuehne + Nagel - Palmeiro, Orlando Nitzke (Universidade do Vale do Rio dos Sinos, 2015)
This work aimed to analyze the bottlenecks identified in the storage process of a 3PL (third-party logistics), a logistics multinational operator, for a large chemical industry. The research was a qualitative using a single case study at Kuehne + Nagel. The evidence sources used were interviews with Kuehne + Nagel members and the chemical industry, document analysis and direct observation in the warehouse. According to the analysis, it was found that there are opportunities for improvement both sides. The results obtained by analyzing the operation storage at Kuehne + Nagel identified problems related to the allocation of materials at bins (as the dimensions, weights and movement of the items), address no automated, material separation area (picking) unidentified , speed in the delivery of applications for separation and subsequent shipment, industrial handling equipment in insufficient quantities, internal accessibility to operations procedures and automation of internal storage operations. These process differences served to guide immediate and future operational activities in the organization, aiming to improve the level of service. At the end of the study is proposed, based on the opportunities identified improvements and bottlenecks, the 5W2H listing the actions to be taken. After these actions are prioritized through a GUT Matrix (Gravity, Urgency and Trend).
Keywords: Armazenagem; Logística; Terceirização da armazenagem; 3PL; PSL; Storage; Logistics; Outsourcing of warehouse; ACCNPQ::Ciências Sociais Aplicadas::Administração